Impact of Certain Egyptian Wax Foundation Types and Their Chemical Composition on Biological Activities of Honey Bees - Abd El-Wahab, T. E.; Zidan, E. W.; Ghania, A. M. M. (International Journal of Agricultural Technology, 2018)
The quality of certain beeswax foundation sheets locally marketed that named by Etman, Mady and Nasr and natural beeswax secretion by bees was determined. Quality was evaluated which based on the effect of beeswax foundation sheets on the biological activities of honey bee colonies. Also, the chemical analysis of these natural beeswax or foundation sheets was detected by Gas Chromatography (GC) and Mass Spectrometry (MS).Those parameters were carried out all through unique blooming seasons of citrus, clover and black cumin in three governorates of Egypt. In April season the studies showed significant differences in the average area of comb built (drawn) by honey bee colonies after one month in Qalubia region. Also, at the same region a significant area of wax cells built were used for worker brood in Mady beeswax foundation followed by Etman and Nasr beeswax foundation. Mady wax foundation had a significant area of honey stored at Qalubia region. Tested colonies at Beni Sauef built a highly area of wax cells (243.3 inch²) of Etman wax foundation followed by Assiut (203.3 inch²) and Qalubia region (133.6 inch²). In June period Beni Sauef recorded a significant value of natural secreted wax cells (373.33 inch²) followed by of Assiut (350 inch²) and Qalubia (221.66 inch²) after one month of test technique. It is noticed that the natural secreted wax cells were used for worker brood rearing at Qalubia region. Results indicated that during June period bee workers in the tested colonies used natural secreted wax cells for honey stored and drone brood rearing at Beni Sauef and Assiut regions.